(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Global health care prices have been rising at an alarming rate, and a large amount of these expenses can be traced to operational inefficiencies related to the administrative and direct medical service delivery procedures. Costs connected to the "overuse," "underuse," or "misuse" of health care resources are thought to total more than half a trillion dollars annually. Consequently, a less detrimental and more effective method of controlling health care costs is focused on reducing "waste" of resources rather than lowering value-added services by lowering payment levels, benefit structures, and eligibility. It is not unexpected that the health care industry is entangled in severe crises pertaining to safety, quality, cost, and access that seriously jeopardize the health and well-being of numerous people given the existing state of "broken" health care procedures and system failures. This study looked at the variables that affect how well health services are provided in public hospitals in the Kingdom of Saudi Arabia (KSA) as well as possible solutions.